Genetic diversity in Indian wheat cultivars for resistance to leaf and stripe rust - PRASHAR; S.K. NAYAR, RAJBIR YADAV*, J. KUMAR, (Indian Phytopathology, 2007)
Genetic diversity in the released varieties of wheat against the prevailing diseases has stabilized the productions over the years. Wheat varieties grown in Northwestern plain zone of India like PBW 343, WH 542, UP 2338 and PBW 373 were screened for their resistance against leaf and stripe rust. Virulence for leaf and stripe rust against the most predominating varieties in Northwestern plain zone is available and these varieties are not resistant at adult plant stage against both the diseases. A number of genes like Lr9, Lr19 and Lr24, which are effective against most of the pathotypes of brown rust, are available in the improved genotypes. Three genotypes namely, RRW3, RRW4 and RRW 12 with resistance against leaf and stripe rust and some tolerance against Karnal bunt have been developed as a result of crossing the donors for these genes with high yielding variety WH542.